2020
DOI: 10.4314/gjds.v17i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Trade Credit Contracts, Theories and their Applications: A Synthesis of the Literature

Abstract: The paper studies theories relating to trade credit contracts as well as their applications and limitations, via review and synthesis of the trade credit literature. Using keywords and search phrases, the literature was identified from key economics, business and financedomains. Trade credit contracts are not complex, this can be explained by factors such as shortness of credit period, frequent transactions, proximity and interaction between trading parties, and effective informal enforcement mechanisms. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…A synthetic summary of these considerations can be found in Table 1. As can be inferred from the summary of the trade credit theories collated in Table 1, both from the explanations and repeated literature items, the theories tend to overlap and interrelate rather than be mutually exclusive (Dary, Harvey, 2020). Similar interrelations can be observed in the case of the motives behind trade credit activity.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 70%
“…A synthetic summary of these considerations can be found in Table 1. As can be inferred from the summary of the trade credit theories collated in Table 1, both from the explanations and repeated literature items, the theories tend to overlap and interrelate rather than be mutually exclusive (Dary, Harvey, 2020). Similar interrelations can be observed in the case of the motives behind trade credit activity.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 70%
“…This conclusion is comparable to that reported in the research on inventory management by Rai et al (2023) demonstrating adequate financial aid in material flow optimization and profitability. Further research by Dary and James Jr (2020) carried out experiments and confirmed that enterprises concurrently provide credit, indicating that the gap between prepayments and creditors needs to be appropriately evaluated and funded to maximize profitability. Moderating variable firm characteristics was assessed using firm size and firm capital structure.…”
Section: Methodsmentioning
confidence: 97%
“…Although trade credit is usually unsecured and its repayment enforcement through the courts can be problematic (Troya-Martínez, 2017), undoubtedly, one of the mechanisms aimed at mitigating the above-mentioned problems and increasing confidence are judicial institutions (Dary & James, 2020). Since lenders do not have full information on borrowers and contracts are incomplete, the presence of a third party responsible for the legislation and its enforcement is central to credit transactions.…”
Section: Judicial Efficiency and Trade Credit Theoretical Considerati...mentioning
confidence: 99%